Основные направления развития методики исследований процессов механической обработки отверстий в различных материалах - Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2006)
The base direction of development of the research technique for occurrence and the passing of physical phenomena in cutting area and also in tool zone at drilling of deep holes in different materials, and also their interaction among themselves, is offered. It is represented the general mathematical model, which describes the interaction of these physical phenomena. On the basis of the mathematical model the creation of application software, is possible. Usage of the application software will allow speeding up the investigation of cutting processes, so to increase labor productivity in production, and to cut down ex-penses of scientific investigations on the given subject.
Keywords: машиностроение; модернизация; точечный мгновенный источник; тепловіделение; модель математическая